PENGARUH PEMBERIAN BROWNIES TEMBUL (TEPUNG TEMPE DAN TEPUNG BEKATUL) SEBAGAI MAKANAN SELINGAN TINGGI SERAT TERHADAP PENURUNAN BERAT BADAN REMAJA OBESITAS - Diyanah Fradani Mareta; afriyana siregar (Poltekkes Kemenkes Bengkulu, 2026)
Adolescent obesity is an increasing health problem in Indonesia and contributes to various degenerative diseases. One approach to lose weight is to consume high-fiber foods. Tembul brownies, made from a combination of tempeh flour and bran flour, are an alternative snack with high fiber and have the potential to help lose weight. This study aims to determine the effect of giving tembul brownies as a high-fiber snack on weight loss in obese adolescents. The sampling method used was the Stratafied Random Sampling technique with a quasi-experimental design with a two-group pretest-posttest design. The subjects of the study were 62 obese adolescents at SMA Muhammadiyah 1 Palembang and SMA Negeri 6 Palembang who were divided into treatment and comparison groups. The treatment group was given tembul brownies twice a day as much as 50 grams for 21 days. The data collected included body weight, macronutrient intake, and fiber, and were analyzed using appropriate statistical tests. The average weight before treatment was 88.13 kg and after treatment was 87.79 kg with an average decrease of 0.335 kg. The results of the paired t-test showed a pvalue of 0.001 (<0.05) which indicates that there is an effect of giving tembul brownies on weight loss in obese adolescents. There is an effect of giving tembul brownies (tempeh flour and bran flour) as a high-fiber snack on weight loss in obese adolescents.